Resin as well as preparation method and application thereof

The polyurethane resin prepared by hydrogen silicon addition reaction is used as a dispersant to solve the problems of uneven dispersion of conductive fillers and high viscosity of conductive paste, and improves conductive properties and reduces viscosity. It is suitable for the printing process of solar cells.

CN119842079AActive Publication Date: 2025-04-18GUANGZHOU HAOYI NEW MATERIALS TECHNOLOGY CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510329991.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

It is difficult for the existing dispersant to maintain the uniformity of the dispersion of the conductive filler during long-term storage, which affects the electrical properties of the conductive paste. Moreover, the viscosity of the conductive paste is high and difficult to print.

Method used

A polyurethane resin prepared by hydrogen silicon addition reaction is used as a dispersant, and the dispersion effect of the resin is enhanced by introducing silicone segments and crosslinked with other resin components in the conductive paste under baking conditions to form a more stable structure.

Benefits of technology

The good dispersion effect of conductive fillers in conductive paste is achieved, the conductive performance is improved, and the viscosity of conductive paste is reduced, making it more suitable for printing applications, while maintaining good dispersion after long-term storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842079A_ABST
    Figure CN119842079A_ABST
Patent Text Reader

Abstract

The invention provides resin and a preparation method and application thereof, and the preparation method comprises the following steps: carrying out first reaction on a monomer A and first dihydric alcohol to obtain carboxyl-terminated resin; the monomer A comprises unsaturated binary acid and / or unsaturated anhydride; carrying out second reaction on the carboxyl-terminated resin and second dihydric alcohol to obtain third dihydric alcohol; carrying out third reaction on the diisocyanate and a sealing agent to obtain semi-blocked isocyanate; carrying out a fourth reaction on the third dihydric alcohol and the semi-terminated isocyanate to obtain polyurethane resin; and carrying out fifth reaction on the polyurethane resin and single-ended hydrogen-containing silicone oil to obtain the resin. The resin prepared by adopting the preparation method provided by the invention can be used as a dispersing agent of the conductive paste, can play a good dispersing effect on conductive filler in the conductive paste, and can reduce the viscosity of the conductive paste while improving the conductivity of the conductive paste, so that the conductive paste is more beneficial to printing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and in particular relates to a resin and a preparation method and application thereof. Background Art

[0002] Solar energy is one of the important renewable clean energy sources. It has broad development prospects due to its pollution-free, renewable and large storage capacity. Solar cells are electronic devices that use the photoelectric effect to convert light energy into electrical energy. They are one of the most promising new power sources among various power sources. Conductive paste is the key raw material for manufacturing solar cells.

[0003] Since the content of conductive filler in the perovskite stacked heterojunction conductive paste is relatively high, the amount of conductive filler added is generally 88-94%, so the dispersion effect of the conductive filler is particularly high. CN116665948A discloses a low-temperature silver paste for HJT solar cells, including: silver powder accounting for 92% of the total mass of the silver paste, organic carrier accounting for 7.2% of the total mass of the silver paste, coupling agent accounting for 0.2% of the total mass of the silver paste, dispersant accounting for 0.3% of the total mass of the silver paste, and curing agent accounting for 0.3% of the total mass of the silver paste, wherein the dispersant is polyphosphate BYK110; CN115579171A discloses a low-temperature silver paste for easy-to-weld solar cells, including the following components: 85-92% of silver powder, 3-8% of resin, 3-8% of organic solvent, 0.2-1.5% of curing agent, 0.2-1% of dispersant, and 0.5-2% of adhesion promoter, wherein the dispersant includes one or more of polyester and polyurethane.

[0004] Although the existing dispersants have a certain degree of wettability for conductive fillers and can reduce the viscosity of the conductive slurry after three rolls, there is still a problem of uneven dispersion of the conductive fillers during long-term storage, and it will also affect the electrical properties of the conductive slurry. Therefore, it is urgent to provide a dispersant that has a good dispersing effect on the conductive filler, can improve the conductive properties of the conductive slurry, and reduce the viscosity of the conductive slurry. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a resin and a preparation method and application thereof. Through the design of preparation raw materials and processes, the obtained resin can be used as a dispersant for conductive paste, which can have a good dispersing effect on the conductive filler in the conductive paste, and while improving the conductive properties of the conductive paste, it can also reduce the viscosity of the conductive paste, making it more conducive to printing.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a resin, the preparation method comprising:

[0008] Monomer A and a first diol undergo a first reaction to obtain a carboxyl-terminated resin; the monomer A comprises an unsaturated dibasic acid and / or an unsaturated acid anhydride;

[0009] The carboxyl-terminated resin and the second diol undergo a second reaction to obtain a third diol;

[0010] The diisocyanate and the blocking agent undergo a third reaction to obtain a semi-blocked isocyanate;

[0011] The third diol and the semi-blocked isocyanate undergo a fourth reaction to obtain a polyurethane resin;

[0012] The polyurethane resin and the single-terminal hydrogen-containing silicone oil undergo a fifth reaction to obtain the resin.

[0013] The resin main chain segment provided by the present invention adopts a non-polar conventional resin chain segment to enhance the binding ability with other resin components in the conductive paste, and introduces a large number of organosilicon segments through a silylation reaction, so that the resin has a comb-like structure. In addition, the organosilicon segment can increase the wetting effect on the conductive filler in the conductive paste, thereby having a good dispersing effect on the conductive filler, and while improving the conductive performance of the conductive paste, it can also reduce the viscosity of the conductive paste, making it more conducive to printing. After the conductive paste is printed, when the baking temperature exceeds 100°C, the resin provided by the present invention can release -NCO groups in the presence of active hydrogen to further cross-link with other resin components in the conductive paste, thereby becoming a part of other resin components. After the conductive paste using the resin provided by the present invention is stored for a long time, it still has a good dispersing effect on the conductive filler.

[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] As a preferred technical solution, the unsaturated dibasic acid includes maleic acid.

[0016] Preferably, the unsaturated anhydride comprises maleic anhydride and / or tetrahydrophthalic anhydride.

[0017] Preferably, the first diol includes any one of diethylene glycol, dipropylene glycol, 1,6-hexanediol, polyethylene glycol or polypropylene glycol, or a combination of at least two thereof, and more preferably diethylene glycol and / or dipropylene glycol.

[0018] Preferably, the number average molecular weight of the polyethylene glycol and the polypropylene glycol is independently 200-400, for example, 220, 240, 260, 280, 300, 320, 340, 360, 380, etc.

[0019] Preferably, the molar ratio of the first diol to monomer A is (1-1.1):1, for example, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1, 1.09:1, etc.

[0020] Preferably, the temperature of the first reaction is 80-100°C, for example, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C, etc.

[0021] Preferably, the time of the first reaction is 4-10 h, for example, it can be 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, etc.

[0022] Preferably, the first reaction is carried out in the presence of a catalyst and / or an inhibitor.

[0023] Preferably, the catalyst comprises p-toluenesulfonic acid and / or dodecylbenzenesulfonic acid.

[0024] Preferably, based on the total mass of the monomer A and the first diol as 100%, the mass of the catalyst is 0.4-0.8%, for example, it may be 0.42%, 0.45%, 0.48%, 0.5%, 0.52%, 0.55%, 0.58%, 0.6%, 0.62%, 0.65%, 0.68%, 0.7%, 0.72%, 0.75%, 0.78%, etc.

[0025] Preferably, the polymerization inhibitor comprises butylated hydroxytoluene.

[0026] Preferably, based on the total mass of the monomer A and the first diol as 100%, the mass of the inhibitor is 0.1-0.2%, for example, it can be 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, etc.

[0027] Preferably, dry air is continuously introduced during the first reaction.

[0028] Preferably, the second diol includes any one of 1,3-propylene glycol, 1,4-butylene glycol or 1,6-hexanediol, or a combination of at least two thereof.

[0029] Preferably, the molar ratio of the carboxyl group of the carboxyl-terminated resin to the hydroxyl group of the second diol is 1:(1.2-1.5), for example, it can be 1:1.22, 1:1.25, 1:1.28, 1:1.3, 1:1.32, 1:1.35, 1:1.38, 1:1.4, 1:1.42, 1:1.45, 1:1.48, etc.

[0030] Preferably, the temperature of the second reaction is 105-115°C, for example, it can be 106°C, 107°C, 108°C, 109°C, 110°C, 111°C, 112°C, 113°C, 114°C, etc.

[0031] Preferably, the second reaction is carried out until the acid value of the reaction system is less than 5 mgKOH / g (for example, 4.5 mgKOH / g, 4.2 mgKOH / g, 4 mgKOH / g, 3.5 mgKOH / g, 3.2 mgKOH / g, 3 mgKOH / g, 2.5 mgKOH / g, 2.2 mgKOH / g, 2 mgKOH / g, 1.5 mgKOH / g, 1.2 mgKOH / g, 1 mgKOH / g, 0.5 mgKOH / g, 0.2 mgKOH / g, etc.).

[0032] Preferably, the hydroxyl value of the third diol is 60-150 mgKOH / g, for example, 62 mgKOH / g, 64 mgKOH / g, 66 mgKOH / g, 68 mgKOH / g, 70 mgKOH / g, 72 mgKOH / g, 74 mgKOH / g, 76 mgKOH / g, 78 mgKOH / g, 80 mgKOH / g, 82 mgKOH / g, 84 mgKOH / g, 86 mgKOH / g. g, 88mgKOH / g, 90mgKOH / g, 92mgKOH / g, 94mgKOH / g, 95mgKOH / g, 100mgKOH / g, 105mgKOH / g, 110mgKO H / g, 115mgKOH / g, 120mgKOH / g, 125mgKOH / g, 130mgKOH / g, 135mgKOH / g, 140mgKOH / g, 145mgKOH / g, etc.

[0033] Preferably, the diisocyanate includes any one of meta-xylylene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate or dicyclohexylmethane diisocyanate, or a combination of at least two thereof.

[0034] Preferably, the blocking agent comprises glycerol carbonate and / or diisopropylamine.

[0035] Preferably, the molar ratio of the blocking agent to the diisocyanate is 1:(2-4), for example, it can be 1:2.2, 1:2.4, 1:2.6, 1:2.8, 1:3, 1:3.2, 1:3.4, 1:3.6, 1:3.8, etc.

[0036] Preferably, the temperature of the third reaction is 70-78°C, for example, it can be 70.5°C, 71°C, 71.5°C, 72°C, 72.5°C, 73°C, 73.5°C, 74°C, 74.5°C, 75°C, 75.5°C, 76°C, 76.5°C, 77°C, 77.5°C, etc.

[0037] Preferably, the time of the third reaction is 6-12 h, for example, it can be 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h, etc.

[0038] Preferably, the third reaction is carried out in the presence of an organic amine catalyst.

[0039] For example, the organic amine catalyst can be purchased from Tosoh and Evonik of Japan.

[0040] Preferably, based on 100% of the mass of the diisocyanate, the mass of the organic amine catalyst is 0.05-0.2%, for example, 0.06%, 0.08%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, etc.

[0041] Preferably, the molar ratio of the third diol to the semi-blocked isocyanate is (1-1.05):1, for example, it may be 1.01:1, 1.02:1, 1.03:1, 1.04:1, etc.

[0042] Preferably, the temperature of the fourth reaction is 60-75°C, for example, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, etc.

[0043] Preferably, the time of the fourth reaction is 10-18 h, for example, it can be 10.5 h, 11 h, 11.5 h, 12 h, 12.5 h, 13 h, 13.5 h, 14 h, 14.5 h, 15 h, 15.5 h, 16 h, 16.5 h, 17 h, 17.5 h, etc.

[0044] Preferably, the fourth reaction further comprises a purification step after completion.

[0045] Preferably, the purification method comprises: washing the reaction product with ether for 2-3 times, and then removing the ether by reduced pressure distillation at 80° C. to obtain a polyurethane resin with higher purity.

[0046] Preferably, the number average molecular weight of the single-ended hydrogen-containing silicone oil is 500-800, for example, it can be 520, 540, 560, 580, 600, 620, 640, 660, 680, 700, 720, 740, 760, 780, etc.

[0047] Preferably, the mass ratio of the polyurethane resin to the single-ended hydrogenated silicone oil is 100:(10-18), for example, it can be 100:10.5, 100:11, 100:11.5, 100:12, 100:12.5, 100:13, 100:13.5, 100:14, 100:14.5, 100:15, 100:15.5, 100:16, 100:16.5, 100:17, 100:17.5, etc.

[0048] Preferably, the temperature of the fifth reaction is 90-110°C, for example, it may be 92°C, 94°C, 96°C, 98°C, 100°C, 102°C, 104°C, 106°C, 108°C, etc.

[0049] Preferably, the time of the fifth reaction is 6-10 h, for example, it can be 6.2 h, 6.5 h, 6.8 h, 7 h, 7.2 h, 7.5 h, 7.8 h, 8 h, 8.2 h, 8.5 h, 8.8 h, 9 h, 9.2 h, 9.5 h, 9.8 h, etc.

[0050] Preferably, the fifth reaction is carried out in the presence of a Custer catalyst.

[0051] Preferably, based on the mass of the single-ended hydrogen-containing silicone oil as 100%, the mass of the Castel catalyst is 0.03-0.05%, for example, it may be 0.032%, 0.034%, 0.036%, 0.038%, 0.04%, 0.042%, 0.044%, 0.046%, 0.048%, etc.

[0052] Preferably, the fifth reaction is carried out in an organic solvent.

[0053] Preferably, the organic solvent comprises ethylene glycol butyl ether acetate and / or diethylene glycol butyl ether acetate.

[0054] Preferably, based on the total mass of the polyurethane resin and the single-ended hydrogenated silicone oil as 100%, the mass of the organic solvent is 30-40%, for example, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, etc.

[0055] Preferably, the preparation method specifically comprises the following steps:

[0056] (1) Monomer A, a first diol, a catalyst and a polymerization inhibitor are reacted at 80-100° C. for 4-10 hours to obtain a carboxyl-terminated resin, and dry air is continuously introduced during the reaction; the monomer A comprises an unsaturated dibasic acid and / or an unsaturated acid anhydride; the molar ratio of the first diol to the monomer A is (1-1.1):1; based on the total mass of the monomer A and the first diol as 100%, the mass of the catalyst is 0.4-0.8%, and the mass of the polymerization inhibitor is 0.1-0.2%;

[0057] (2) the carboxyl-terminated resin reacts with the second diol at 105-115° C. until the acid value of the reaction system is less than 5 mgKOH / g, thereby obtaining a third diol having a hydroxyl value of 60-150 mgKOH / g; the molar ratio of the carboxyl group of the carboxyl-terminated resin to the hydroxyl group of the second diol is 1:(1.2-1.5);

[0058] (3) reacting a diisocyanate, a blocking agent and an organic amine catalyst at 70-78° C. for 6-12 hours to obtain a semi-blocked isocyanate; the molar ratio of the blocking agent to the diisocyanate is 1:(2-4); based on the mass of the diisocyanate being 100%, the mass of the organic amine catalyst is 0.05-0.2%;

[0059] (4) The third diol and the semi-blocked isocyanate are reacted at 60-75° C. for 10-18 hours, the reaction product is washed with ether 2-3 times, and the ether is removed by reduced pressure distillation at 80° C. to obtain a polyurethane resin; the molar ratio of the third diol to the semi-blocked isocyanate is (1-1.05):1;

[0060] (5) The polyurethane resin, single-ended hydrogenated silicone oil, Castell catalyst and organic solvent are reacted at 90-110° C. for 6-10 hours to obtain the resin; the mass ratio of the polyurethane resin to the single-ended hydrogenated silicone oil is 100:(10-18); based on the total mass of the polyurethane resin and the single-ended hydrogenated silicone oil being 100%, the mass of the organic solvent is 30-40%; based on the mass of the single-ended hydrogenated silicone oil being 100%, the mass of the Castell catalyst is 0.03-0.05%.

[0061] In a second aspect, the present invention provides a resin, which is prepared by the preparation method described in the first aspect.

[0062] In a third aspect, the present invention provides a conductive paste, wherein the conductive paste comprises the resin as described in the second aspect.

[0063] Preferably, the mass percentage of the resin as described in the second aspect in the conductive paste is 1-1.5%, for example, it may be 1.05%, 1.1%, 1.15%, 1.2%, 1.25%, 1.3%, 1.35%, 1.4%, 1.45%, etc.

[0064] Preferably, the conductive paste further comprises a conductive filler; the conductive filler comprises any one of copper powder, silver powder or silver-coated copper powder or a combination of at least two thereof.

[0065] In a fourth aspect, the present invention provides a use of the conductive paste as described in the third aspect in a perovskite stacked heterojunction solar cell.

[0066] Compared with the prior art, the present invention has the following beneficial effects:

[0067] The resin prepared by the preparation method provided by the present invention can be used as a dispersant for conductive paste, which can increase the wetting effect on the conductive filler in the conductive paste, thereby having a good dispersing effect on the conductive filler, and while improving the conductive performance of the conductive paste, it can also reduce the viscosity of the conductive paste, making it more conducive to printing; in addition, after the conductive paste using the resin provided by the present invention is printed, when the baking temperature exceeds 100°C, the resin provided by the present invention can release -NCO groups in the presence of active hydrogen, and further cross-link with other resin components in the conductive paste, thereby becoming a part of other resin components. The conductive paste using the resin provided by the present invention as a dispersant has an initial viscosity of 13-42 Pa·s at 25°C, and a viscosity of 18-51 Pa·s after being placed for 72 hours; after printing the conductive paste, the initial line resistance is 353-880Ω, and the line resistance after being placed for 72 hours is 367-960Ω. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 is the infrared spectrum of the carboxyl-terminated resin in Example 1;

[0069] Figure 2 is the infrared spectrum of the third diol in Example 1;

[0070] Figure 3 is the infrared spectrum of the semi-blocked isocyanate in Example 1;

[0071] Figure 4 is the infrared spectrum of the polyurethane resin in Example 1;

[0072] Figure 5 It is the infrared spectrum of the resin provided in Example 1. DETAILED DESCRIPTION

[0073] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0074] The sources of some components in the following examples and comparative examples are as follows:

[0075] (1) Organic amine catalyst: purchased from Tosoh, Japan, L33B;

[0076] (2) Single-ended hydrogenated silicone oil: The following single-ended hydrogenated silicone oils were purchased from Siwansi Materials Technology Nantong Co., Ltd.;

[0077] Single-ended hydrogen-containing silicone oil A, number average molecular weight is 500;

[0078] Single-ended hydrogen-containing silicone oil B, number average molecular weight is 600;

[0079] Single-ended hydrogen-containing silicone oil C, number average molecular weight is 800;

[0080] Single-ended hydrogen-containing silicone oil D, number average molecular weight is 400;

[0081] Single-ended hydrogen-containing silicone oil E, number average molecular weight is 1200;

[0082] (3) Custer catalyst: purchased from Promised Chemicals, with a platinum content of 1000 ppm.

[0083] In the following examples and comparative examples, the acid value of the reaction system is tested by acid-base titration; the hydroxyl value of the third diol is tested according to GBT 7193.2-1987 "Method for Determination of Hydroxyl Value of Unsaturated Polyester Resins".

[0084] In Example 1, the infrared spectra of each substance were obtained by testing with a Fourier transform infrared spectrometer (manufacturer: Thermo Fisher, model: Summit X).

[0085] Example 1

[0086] A resin and a preparation method thereof, the preparation method comprising the following steps:

[0087] (1) 1 mol of maleic anhydride, 1 mol of diethylene glycol, 1.2 g of p-toluenesulfonic acid and 0.3 g of butylated hydroxytoluene are reacted at 90° C. for 6 h, and dry air is continuously introduced during the reaction to obtain a carboxyl-terminated resin; the infrared spectrum of the carboxyl-terminated resin is as shown in Figure 1 As shown in the figure, it can be seen that 1740cm -1 It is the characteristic absorption peak of C=O in carboxyl group, 3425cm -1 It is the characteristic absorption peak of OH in carboxyl group;

[0088] (2) 1 mol of the carboxyl-terminated resin is reacted with 1.2 mol of 1,3-propylene glycol at 105° C. until the acid value of the reaction system is less than 5 mgKOH / g, thereby obtaining a third diol having a hydroxyl value of 75 mgKOH / g; the infrared spectrum of the third diol is as follows: Figure 2 As shown, it can be seen from the figure that the carboxyl-terminated resin reacts with 1,3-propylene glycol to generate a third diol;

[0089] (3) 2 mol of m-xylylene diisocyanate, 1 mol of glycerol carbonate, and 0.3 g of an organic amine catalyst are reacted at 70° C. for 6 h to obtain a semi-blocked isocyanate; the infrared spectrum of the semi-blocked isocyanate is as follows: Figure 3 As shown in the figure, it can be seen that 2260cm -1 is the characteristic absorption peak of -NCO group, 3350cm -1 It is the characteristic absorption peak of NH, which proves that semi-blocked isocyanate is prepared;

[0090] (4) After 1 mol of the third diol and 1 mol of the semi-blocked isocyanate are reacted at 65° C. for 10 h, the reaction product is washed twice with ether, and then the ether is removed by reduced pressure distillation at 80° C. to obtain a polyurethane resin; the infrared spectrum of the polyurethane resin is as follows: Figure 4 As shown in the figure, it can be seen that the characteristic absorption peak of -NCO disappears, indicating that polyurethane resin is generated;

[0091] (5) 100 parts by weight of the polyurethane resin, 14 parts by weight of single-end hydrogenated silicone oil A, 0.006 parts by weight of Custer catalyst and 35 parts by weight of ethylene glycol butyl ether acetate were reacted at 90° C. for 6 hours to obtain the resin. The infrared spectrum of the resin is as follows: Figure 5 As shown in the figure, it can be seen that the polyurethane resin reacts with the single-end hydrogen-containing silicone oil A to generate a resin.

[0092] Example 2

[0093] A resin and a preparation method thereof, the preparation method comprising the following steps:

[0094] (1) 1 mol of maleic acid, 1 mol of dipropylene glycol, 1.1 g of dodecylbenzenesulfonic acid and 0.3 g of butylated hydroxytoluene were reacted at 90°C for 8 h, with dry air continuously introduced during the reaction, to obtain a carboxyl-terminated resin;

[0095] (2) 1 mol of the carboxyl-terminated resin is reacted with 1.3 mol of 1,6-hexanediol at 110° C. until the acid value of the reaction system is less than 5 mgKOH / g, thereby obtaining a third diol having a hydroxyl value of 102 mgKOH / g;

[0096] (3) 2 mol of isophorone diisocyanate, 1 mol of diisopropylamine, and 0.4 g of an organic amine catalyst were reacted at 74°C for 10 h to obtain a semi-blocked isocyanate;

[0097] (4) 1.05 mol of the third diol and 1 mol of the semi-blocked isocyanate are reacted at 75° C. for 18 hours, the reaction product is washed twice with ether, and then the ether is removed by reduced pressure distillation at 80° C. to obtain a polyurethane resin;

[0098] (5) 100 parts by weight of the polyurethane resin, 10 parts by weight of single-ended hydrogenated silicone oil B, 0.003 parts by weight of Custer catalyst and 40 parts by weight of diethylene glycol butyl ether acetate were reacted at 100° C. for 8 hours to obtain the resin.

[0099] Example 3

[0100] A resin and a preparation method thereof, the preparation method comprising the following steps:

[0101] (1) 1 mol of tetrahydrophthalic anhydride, 1.05 mol of dipropylene glycol, 1.5 g of p-toluenesulfonic acid and 0.5 g of butylated hydroxytoluene were reacted at 90°C for 7 h, with dry air continuously introduced during the reaction, to obtain a carboxyl-terminated resin;

[0102] (2) 1 mol of the carboxyl-terminated resin is reacted with 1.5 mol of 1,4-butanediol at 115° C. until the acid value of the reaction system is less than 5 mgKOH / g, thereby obtaining a third diol having a hydroxyl value of 140 mgKOH / g;

[0103] (3) 4 mol of hexamethylene diisocyanate, 1 mol of glycerol carbonate, and 0.5 g of an organic amine catalyst were reacted at 78°C for 8 h to obtain a semi-blocked isocyanate;

[0104] (4) 1.02 mol of the third diol and 1 mol of the semi-blocked isocyanate are reacted at 75° C. for 16 h, the reaction product is washed with ether three times, and then the ether is removed by reduced pressure distillation at 80° C. to obtain a polyurethane resin;

[0105] (5) 100 parts by weight of the polyurethane resin, 10 parts by weight of single-ended hydrogenated silicone oil C, 0.004 parts by weight of Custer catalyst and 38 parts by weight of ethylene glycol butyl ether acetate were reacted at 110° C. for 10 hours to obtain the resin.

[0106] Example 4

[0107] A resin and a preparation method thereof, which differs from Example 1 only in that in step (1), an equal molar amount of diethylene glycol is replaced by 1,6-hexanediol, and the remaining raw materials, process parameters and steps are the same as those in Example 1.

[0108] Example 5

[0109] A resin and a preparation method thereof, which differs from Example 1 only in that the single-terminal hydrogen-containing silicone oil A of equal mass in step (5) is replaced by single-terminal hydrogen-containing silicone oil D, and the remaining raw materials, process parameters and steps are the same as those in Example 1.

[0110] Example 6

[0111] A resin and a preparation method thereof, which differs from Example 1 only in that the single-terminal hydrogen-containing silicone oil A in step (5) is replaced with single-terminal hydrogen-containing silicone oil E, and the remaining raw materials, process parameters and steps are the same as those in Example 1.

[0112] Example 7

[0113] A resin and a preparation method thereof, which differs from Example 1 only in that the amount of single-end hydrogen-containing silicone oil A used in step (5) is 6 parts by weight, and the remaining raw materials, process parameters and steps are the same as those in Example 1.

[0114] Example 8

[0115] A resin and a preparation method thereof, which differs from Example 1 only in that the amount of single-end hydrogen-containing silicone oil A used in step (5) is 22 parts by weight, and the remaining raw materials, process parameters and steps are the same as those in Example 1.

[0116] Example 9

[0117] A resin and a preparation method thereof, which differs from Example 1 only in that the amount of glycerol carbonate used in step (3) is 0.4 mol, and the remaining raw materials, process parameters and steps are the same as those in Example 1.

[0118] The sources of some components in the following application examples and comparative application examples are as follows:

[0119] (1) Curing agent: HF-9069 purchased from Guangzhou Haoyi New Materials Technology Co., Ltd.;

[0120] (2) Conductive copper powder: purchased from Jiangsu Boqian, Cu-GB3501N;

[0121] (3) Bisphenol F epoxy resin: purchased from Nan Ya Resins, NPEF-170;

[0122] (4) Polyester resin: purchased from Bostik 3300;

[0123] (5) Dispersant: purchased from BYK Chemicals DISPERBYK-108.

[0124] Application Example 1

[0125] A conductive paste, the components of which include 1.3 parts by weight of the resin provided in Example 1, 92 parts by weight of conductive copper powder, 1.8 parts by weight of bisphenol F epoxy resin, 2.5 parts by weight of curing agent HF-9069, 0.8 parts by weight of polyester resin and 1.6 parts by weight of DBE solvent;

[0126] The preparation method of the conductive paste comprises:

[0127] After the above materials are mixed, a three-roller mill is used to stir and disperse them evenly to obtain the conductive paste.

[0128] Application Example 2-9

[0129] A conductive paste and a preparation method thereof, which differs from Application Example 1 only in that the resin and other qualities provided in Example 1 are replaced with the resins provided in Examples 2-9, and the remaining raw materials, process parameters and steps are the same as those in Application Example 1.

[0130] Comparative application example 1

[0131] A conductive paste and a preparation method thereof, which differs from Application Example 1 only in that the resin and other qualities provided in Example 1 are replaced by the polyurethane resin prepared in step (4) of Example 1, and the remaining raw materials, process parameters and steps are the same as those in Application Example 1.

[0132] Comparative Application Example 2

[0133] A conductive paste and a preparation method thereof, which differs from Application Example 1 only in that the resin provided in Example 1 is replaced by a mixture of 1.2 parts by weight of the polyurethane resin prepared in step (4) of Example 1 and 0.1 parts by weight of single-end hydrogen-containing silicone oil A, and the remaining raw materials, process parameters and steps are the same as those in Application Example 1.

[0134] Comparative Application Example 3

[0135] A conductive paste and a preparation method thereof, which differs from Application Example 1 only in that the resin and other qualities provided in Example 1 are replaced with DISPERBYK-108, and the remaining raw materials, process parameters and steps are the same as those in Application Example 1.

[0136] Performance Testing

[0137] (1) Viscosity: Use a rotary viscometer at 200 rpm to test the viscosity of the conductive paste at 25°C. After the conductive paste is left for 72 hours, test its viscosity again.

[0138] (2) Line resistance: Print serpentine circuits on a transparent glass plate with a line width and line spacing of 2 mm, then bake at 160°C for 30 min. After cooling to room temperature, use a resistivity tester (manufacturer: Suzhou Xintonghui, model TH2515) to test the line resistance of the serpentine circuit board. After the serpentine circuit board is left for 72 hours, test its line resistance again.

[0139] The conductive pastes provided in the application examples and comparative application examples were tested according to the above method, and the test results are shown in Table 1 below:

[0140] Table 1

[0141]

[0142] It can be seen from the data in Table 1 that, compared with Comparative Application Example 3, the conductive paste provided by Application Examples 1-3 has a lower initial viscosity and a lower initial line resistance after printing, indicating that the conductive filler is evenly dispersed in the conductive paste. After standing for 72 hours, both the viscosity and the line resistance are small, indicating that the resin provided by the present invention still has a good dispersing effect on the conductive filler.

[0143] It can be seen from Application Example 4 that using polyester-type diols instead of polyether-type diols has little effect on the electrical properties of the conductive paste, but has a greater impact on its viscosity. The reason is that the polyester-type structure is more rigid and not as easy to rotate as the polyether structure, which reduces the viscosity of the conductive paste.

[0144] As can be seen from Application Example 5, the resin prepared using single-end hydrogenated silicone oil with a low number average molecular weight has a low molecular weight of silicone oil segments in the resin structure, resulting in poor dispersion, which leads to increased viscosity of the conductive paste and poor electrical properties. As can be seen from Application Example 6, the resin prepared using single-end hydrogenated silicone oil with a high number average molecular weight has a long silicone oil segment in the resin structure, and the number of comb-like structures of the resin is reduced at the same mass, resulting in increased viscosity of the conductive paste and poor electrical properties.

[0145] It can be seen from Application Example 7 that the dosage of single-ended hydrogen-containing silicone oil is too low, which cannot wet the conductive copper powder, resulting in poor dispersion effect of the resin on the conductive filler; from Application Example 8, it can be seen that the addition amount of single-ended hydrogen-containing silicone oil is too much. Although the dispersion effect of the resin is good and the viscosity stability is good after 72 hours of storage, the proportion of silicone oil in the main chain segment of the resin is too high, and silicone oil is an insulating material, which will cause the resistance value of the conductive paste to increase after printing, thereby reducing its conductive effect.

[0146] It can be seen from Application Example 9 that the amount of sealant used is small, which makes the molecular weight of the resin too large, thereby increasing the viscosity of the conductive paste and causing a poor dispersion effect.

[0147] It can be seen from Comparative Application Example 1 that if the polyurethane resin is not modified by hydrosilylation, the polyurethane resin has a poor dispersion effect on the conductive filler, resulting in a significant increase in the viscosity of the conductive paste and relatively poor electrical properties.

[0148] It can be seen from comparative application example 2 that the method of mixing polyurethane resin with single-ended hydrogen-containing silicone oil causes uneven dispersion of the conductive filler, which increases the viscosity of the conductive paste and leads to poor electrical properties.

[0149] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a resin, characterized in that: The preparation method comprises: Monomer A and a first diol undergo a first reaction to obtain a carboxyl-terminated resin; the monomer A comprises an unsaturated dibasic acid and / or an unsaturated acid anhydride; The carboxyl-terminated resin and the second diol undergo a second reaction to obtain a third diol; The diisocyanate and the blocking agent undergo a third reaction to obtain a semi-blocked isocyanate; The third diol and the semi-blocked isocyanate undergo a fourth reaction to obtain a polyurethane resin; The polyurethane resin and the single-terminal hydrogen-containing silicone oil undergo a fifth reaction to obtain the resin.

2. The preparation method according to claim 1, characterized in that: The unsaturated dibasic acid includes maleic acid; The unsaturated anhydride comprises maleic anhydride and / or tetrahydrophthalic anhydride; The first diol includes any one of diethylene glycol, dipropylene glycol, 1,6-hexanediol, polyethylene glycol or polypropylene glycol, or a combination of at least two thereof.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the first diol to the monomer A is (1-1.1):1; The temperature of the first reaction is 80-100°C; The time of the first reaction is 4-10h; The first reaction is carried out in the presence of a catalyst and / or a polymerization inhibitor.

4. The preparation method according to claim 1, characterized in that: The second diol includes any one of 1,3-propylene glycol, 1,4-butylene glycol or 1,6-hexanediol or a combination of at least two thereof; The molar ratio of the carboxyl group of the carboxyl-terminated resin to the hydroxyl group of the second diol is 1:(1.2-1.5); The temperature of the second reaction is 105-115°C; The second reaction is carried out until the acid value of the reaction system is less than 5 mgKOH / g; The hydroxyl value of the third diol is 60-150 mgKOH / g.

5. The preparation method according to claim 1, characterized in that: The diisocyanate includes any one of meta-xylylene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate or dicyclohexylmethane diisocyanate, or a combination of at least two thereof; The blocking agent includes glycerol carbonate and / or diisopropylamine; The molar ratio of the blocking agent to the diisocyanate is 1:(2-4); The temperature of the third reaction is 70-78°C; The time of the third reaction is 6-12h; The third reaction is carried out in the presence of an organic amine catalyst.

6. The preparation method according to claim 1, characterized in that: The molar ratio of the third diol to the semi-blocked isocyanate is (1-1.05):1; The temperature of the fourth reaction is 60-75°C; The fourth reaction time is 10-18h.

7. The preparation method according to claim 1, characterized in that: The number average molecular weight of the single-ended hydrogen-containing silicone oil is 500-800; The mass ratio of the polyurethane resin to the single-ended hydrogen-containing silicone oil is 100:(10-18); The temperature of the fifth reaction is 90-110°C; The fifth reaction time is 6-10h; The fifth reaction is carried out in the presence of a Custer catalyst.

8. A resin, characterized in that The resin is prepared by the preparation method according to any one of claims 1 to 7.

9. A conductive paste, characterized in that: The conductive paste includes the resin according to claim 8.

10. Use of the conductive paste according to claim 9 in a perovskite stacked heterojunction solar cell.

Citation Information

Patent Citations

  • Solar cell low-temperature silver paste easy to weld and preparation method thereof

    CN115579171A

  • Low-temperature silver paste for HJT solar cell

    CN116665948A

  • Polyurethane synthetic leather resin with good color dispersion and high wear resistance, and preparation method thereof

    CN106751733A

  • Preparation method for amphipathic organosilicon-polyurethane grafted copolymer with comb-like structure

    CN108129636A

  • High-cold-resistance dry-processed polyurethane resin and preparation method thereof

    CN109096463A